Case report: Fatal overwhelming post-splenectomy infection in a patient with metastatic angiosarcoma treated with immunotherapy - Torrado, Carlos; Baysal, Mehmet A.; Chakraborty, Abhijit; Norris, Becky L.; Khawaja, Fareed; Tsimberidou, Apostolia M. (Frontiers in Immunology, 2024)
A patient in his 40s with splenic angiosarcoma metastatic to the liver underwent splenectomy, chemotherapy, and partial hepatectomy before being treated on a clinical trial with CTLA4 and PD1 inhibitors. He had received pneumococcal and meningococcal vaccines post-splenectomy. On week 10, he developed grade 3 immune-related colitis, successfully treated with the anti-tumor necrosis factor-alpha inhibitor infliximab and steroids. After 4 cycles of treatment, scans showed partial response. He resumed anti-PD1 therapy, and 6 hours after the second dose of anti-PD1 he presented to the emergency room with hematemesis, hematochezia, hypotension, fever, and oxygen desaturation. Laboratory tests demonstrated acute renal failure and septicemia (Streptococcus pneumoniae). He died 12 hours after the anti-PD1 infusion from overwhelming post-splenectomy infection (OPSI). Autopsy demonstrated non-viable liver tumors among other findings. In conclusion, patients undergoing immunotherapy and with prior history of asplenia should be monitored closely for OPSI as they may be at increased risk.